Pembangkit Listrik Tenaga Surya Rooftop untuk Perumahan di Pulau Bangka - Raymondo Sianipar; Muhammad Yonggi Puriza; Wahri Sunanda (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
Rooftop Solar Power Plants are an alternative option for environmentally friendly power plants. The application of this technology for the electricity needs of residential areas can be done with the Solar Home System (SHS). One of the roofs that can be used for PV rooftops is the roof of the house in D'Rich Arasel housing with a roof area of 65.5 m². PV Rooftop in D'Rich Arasel housing is designed to meet daily electrical energy needs. The PV rooftop design uses 2 systems, system 1 is a PV mini-grid system based on a daily load that uses 22 units of 250 wp solar panels, 17 units of 150Ah batteries, 1 unit of 3 kW inverter, and 1 unit of solar charge controller 250 A which produces 4077 kWh/year at an investment cost. of Rp. 318,103,346 for 15 years and obtained an NPV value of Rp.-209.932,101. In system 2, namely the PV system based on the entire roof area using 36 units of 200 wp solar panels, 24 units of 150Ah batteries, 1 unit of 8 kW inverter, and 1 unit of a solar charge controller 250 A which produces 12851 kWh/year with an investment cost of Rp. 478,782,406 for 15 years and obtain an NPV value of Rp. 182,529,881.